Improving Article Writing Skills Using the Project Based Learning Model for Semester VI Students - Lili Herawati Parapat; khatib Lubis; Afnan Ali Parapat; Siti Absah (PANTAK: Jurnal Penelitian Tindakan Kelas, 2026)
Article writing competence has become an essential academic skill for university students because it supports scientific communication and publication. However, many students continued to experience difficulties in organising ideas, developing coherent arguments, and producing academic articles that met scholarly standards. Previous studies primarily examined the implementation of Project-Based Learning (PjBL) in science and general language education, while empirical evidence regarding its application in university article writing courses remained limited. Therefore, this study investigated students' learning outcomes following the implementation of the Project-Based Learning model in an Article Writing course.This study employed a quantitative descriptive research design involving 33 sixth-semester students enrolled in the Indonesian Language Education Study Programme. The participants were selected using total sampling. Data were collected through documentation of students' academic achievement, including quiz scores, assignments, practical activities, midterm examination, final examination, and final course grades. The data were analysed using descriptive statistics, including minimum and maximum scores, mean scores, frequency distributions, and percentage analysis.The findings revealed that students achieved satisfactory learning outcomes after the implementation of Project-Based Learning. Most participants obtained excellent academic performance, with 81.82% receiving Grade A, 15.15% obtaining Grade B, and only 3.03% receiving Grade D. The mean final score indicated that students successfully achieved the expected learning outcomes in the Article Writing course. The implementation of Project-Based Learning also promoted active participation, collaborative learning, independent inquiry, and systematic engagement throughout the academic writing process.The findings suggested that Project-Based Learning provided an effective instructional approach for supporting article writing instruction in higher education. This study contributed empirical evidence supporting the integration of project-based instructional strategies into academic writing courses to enhance students' learning achievement and engagement.